Functional genomics-based studies of the microbial ecology of hyperthermophilic micro-organisms. (1st April 2004) - Johnson, M.R.; Montero, C.I.; Conners, S.B.; Shockley, K.R.; Pysz, M.A.; Kelly, R.M.
Abstract : Although much attention has been paid to the genetic, biochemical and physiological aspects of individual hyperthermophiles, how these unique micro-organisms relate to each other and to their natural habitats must be addressed in order to develop a comprehensive understanding of life at high temperatures. Phylogenetic 16 S rRNA-based profiling of samples from various geothermal sites has provided insights into community structure, but this must be complemented with efforts to relate metabolic strategies to biotic and abiotic characteristics in high-temperature habitats. Described here are functional genomics-based approaches, using cDNA microarrays, to gain insight into how ecological features such as biofilm formation, species interaction, and possibly even gene transfer may occur in native environments, as well as to determine what genes or sets of genes may be tied to environmental functionality.